The elastic undrained modulus Eu50 for stiff consolidated clays related to the concept of stress history and normalized soil properties - Stróżyk Joanna (Studia Geotechnica et Mechanica, 2016)
The paper presents the results of a triaxial test conducted on stiff, consolidated clays. The standard TXCIU procedure (isotropic consolidation and undrained shearing) was applied in the laboratory soil tests. The undrained elastic modulus Eu50 was determined from each test.